Tentative characterization of precursor compounds and co-factors of pigment formation in production of 'wu mi' from Vaccinium bracteatum Thunb. Leaves. (1st October 2018) - Fan, Mingcong; Fan, Yihui; Huang, Weiping; Wang, Li; Li, Yan; Qian, Haifeng; Zhang, Hui; Qi, Xiguang
Highlights: Six iridoid glycosides were tentatively identified as the precursors of pigment. L ∗ and b ∗ values of 'Wu mi' increased as VBTL ripening. The pH and β-glucosidase were regarded as the key co-factors for the pigments. A tentative hypothesis of transformation mechanism about the precursor compounds was presented. Abstract: Vaccinium bracteatum leaves (VBTL) are traditionally used in China to dye rice grains, which assume a deep blue color, named 'Wu mi'. Information on the mechanism of pigment formation is limited. In this study, CIELAB color space parameters were used to represent the color of 'Wu mi'. Precursor compounds of pigments formed during the dyeing process were identified by UPLC Q-TOF MS analysis. The changes in co-factors for pigment formation in VBTL were measured at different growth stages. The L ∗ and b ∗ values of dyed rice increased as the leaves aged, whereas a ∗ values showed irregular changes. Six compounds were tentatively identified as pigment precursors by UPLC Q-TOF MS analysis. The pH and β-glucosidase activity at different growth stages of VBTL were indicated to be crucial co-factors for pigment formation. A tentative hypothesis is presented that iridoid glycosides are hydrolyzed by acids and β-glucosidases to form a dialdehyde structure that binds covalently with amino residues of lysine side chains in rice protein molecules.